Exposição e susceptibilidade ao vírus da hepatite B em população vivendo em situação de pobreza na região metropolitana de Goiânia - Silva, Lara Cristina da Cunha Guimarães (2017)
INTRODUCTION: Infection caused by hepatitis B virus (HBV) is considered a major public health problem in several countries, especially in less developed countries. It is estimated that 70% of new chronic infections occur in regions of low-income countries. OBJECTIVE: To evaluate the exposure profile to hepatitis B virus in a population living in poverty in the metropolitan region of Goiânia. METHOD: This is a serological survey of a low-income population. Data collection was performed between August and December 2016. Serological markers for hepatitis B virus (HBV), HBsAg, total anti-HBc, anti-HBc IgM and anti-HBs were investigated, and detected by enzymelinked immunosorbent assay. Continuous variables were presented in median and interquartile ranges (IQR), and categorical variables in absolute and relative frequencies. Bivariate analysis was performed to verify the potential factors associated with exposure to HBV. Variables with p < 0.20 were included in a Poisson regression model with robust variance. Variables with p < 0.05 were considered statistically significant in the multivariate analysis. RESULTS:This study included 378 individual participants from 217 residences. The global prevalence of HBV was 10.6% (95% CI: 7.86-14.09). Acute or chronic infection was identified in 0.8% (95% CI: 0.3-2.4); exposure to HBV confirmed by the presence of immunity markers occurred in 7.7% (95% CI: 5.4-10.9). Isolated Anti-HBc was found in 2.1% (95% CI: 1.1-4.2) of the population. Isolated positivity for anti-HBs was identified in 25.4% (95% CI: 21.3-30.0). In multivariate analysis, it was verified that age (adjusted PR [PRadj]: 1.04; 95% CI: 1.01-1.07), female sex (PRadj: 2.18; 95% CI: 1.01-4.73), sexual relations under the effects of alcohol (PRadj: 2.49; 95% CI: 1.09-5.67) and exposure to Treponema Pallidum (PRadj: 3.10; 95% CI: 1.36-7.06) were associated with exposure to HBV. CONCLUSIONS: These findings indicate significant viral circulation in the study population, aggravated by low serological evidence of immunization against hepatitis B, highlighting the challenge faced by Public Health Services in reaching marginal populations. This can contribute to the perpetuation of cycles of poverty and disease.